Psikoneuroimunologi Depresi pada Polycystic Ovary Syndrome (PCOS) - Yuliadha, Asti; Setyaningrum, Rohmaningtyas Hidayah (Faculty of Medicine Universitas Sebelas Maret, 2022)
Introduction: Polycystic ovary syndrome (PCOS) is heterogeneous, complex endocrine disorder with unknown etiology, affecting 4%−18% of reproductive age women and associated with reproductive, metabolic and psychological dysfunction. Along with physical disorders, many mental disorders are also associated with PCOS, about 40% of women with PCOS have depression. This literature review aims to explore how PCOS can lead to depression in term of psychoneuroimmunology aspects.Method: Literature review was conducted through search engine from Google Scholar and Clinical Key with keywords “Polycystic ovary syndrome”, “depression”, “psychoneuroimmunology”, “distress”, and “inflammation” from 2015-2020.Result: The important role of the HPG axis in the pathophysiology of mood disorder has concluded that high comorbidity between depression and PCOS are caused by hyperandrogenism and insulin resistance mediated by low grade chronic inflammation. The activation of HPA by stress exerts an inhibitory effect on the female reproductive system. CRH can inhibit GnRH secretion from the hypothalamus. The anti-reproductive action of CRH in the ovaries of women with high psychosocial stress lead to early ovarian failure. In addition, the pathophysiology of depression and mental stress in PCOS is associated with various changes including high activity of pro-inflammation markers and the body's immune system during stress, it has also been linked to increased cortisol levels, increased sympathetic activity and decreased serotonin levels in the central nervous system.Result: There’s close relationship between PCOS and depression in terms of psychoneuroimmunology aspects, by HPG axis role. Comprehensive management of depression is improving outcome strategy in women with PCOS by involving CLP.Keywords: Polycystic ovary syndrome (PCOS), Depression, Psychoneuroimmunology, HPG axis